Gene Expression of ECA2 Receptors in the Oral Cavity and Salivary Glands and Its Role in SARS CoV2 Infection. Literature Review - Villanueva-Sánchez, Francisco Germán; Avelar-Juárez, Karla Mayela; Pérez-Cornejo, Nancy; Cruz-Monroy, Eduardo Alonso; Ramos-Baena, José David (Odovtos - International Journal of Dental Sciences, 2020)
ECA2 receptors have an important gene expression in the squamous cells of the tongue and salivary glands, a mechanism that is convenient for the inoculation of SARS CoV2 since it seeks to make the assembly complex through its glycoprotein or spike protein towards the ECA2 receptor of the oral mucosa. Once inoculated and favored by proteases, it is the key that allows the entry of the virion into the host cell for its subsequent replication, increase of viral load and potential deamination and infection; dental professionals must be alert to the mechanisms of infection in the oral cavity for their own protection and that of the patients who are treated by this health personnel.